The importance of aboveground–belowground interactions on the evolution and maintenance of variation in plant defense traits - van Geem, Moniek; Gols, Rieta; van Dam, Nicole M.; van der Putten, Wim H.; Fortuna, Taiadjana; Harvey, Jeffrey A. (Frontiers in Plant Science, 2013)
Over the past two decades a growing body of empirical research has shown that many ecological processes are mediated by a complex array of indirect interactions occurring between rhizosphere-inhabiting organisms and those found on aboveground plant parts. Aboveground - belowground studies have thus far focused on elucidating processes and underlying mechanisms that mediate the behavior and performance of invertebrates in opposite compartments. Less is known about genetic variation in plant traits as this applies to an above- belowground framework. For instance, although the field of genetic variation in aboveground plant traits on community-level interactions is well developed, most studies have ignored genetic variation in plant traits – such as defence - that may have evolved in response to pressures from the combined effects of above- and below ground interactions from antagonists and mutualists. Here, we discuss gaps in our understanding of genetic variation in plant- and consumer-related traits as they relate to aboveground and belowground multitrophic interactions. When metabolic resources are limiting, then multiple attack by antagonists in both domains may lead to trade-offs in where these resources are optimally invested. In nature, these trade-offs may critically depend upon their effects on plant fitness. Natural enemies of herbivores may also influence selection for different traits via top-down control. At larger scales these interactions may generate evolutionary ‘hotspots’ where the expression of various plant traits is the result of strong reciprocal selection via direct and indirect interactions. The role of abiotic factors in driving genetic variation in plant traits is also discussed.